A new species of troglobitic freshwater prawn of the genus Macrobrachium Bate, 1868 (Crustacea: Decapoda: Palaemonidae) from Phong Nha-Ke Bang national park, Quang Binh province - Tu, Do Van; Cuong, Nguyen Tong (Academia Journal of Biology, 2015)
Macrobrachium phongnhaense sp. n. is a new species of troglobitic shrimp discovered in some caves of Phong Nha-Ke Bang National Park, Quang Binh province, Vietnam (figure 1-2). Table 1. Coparative morphologcal characteristics of M. phongnhaense sp. n., from Phong Nha-Ke Bang National Park, Vietnam and two other species M. lingyunense J. Li, Cai & Clarke, 2006 and M. elegantum Pan, Hou & Li, 2010, from China Characteristics M. phongnhaense M. lingyunense M. elegantum Rostrum Rostrum sort, not exceeding third segment of antennular peduncle Rostrum reaching distal margin of scaphocerite   Rostrum reaching beyond distal margin of scaphocerite Rostrum tip not bifurcate Rostrum with tip bifurcate Rostrum tip not bifurcate Rostrum formula (rostral teeth on carapace behind the orbit + upper rostral teeth/lower rostral teeth): 1-3+4-7+/0-2 Rostrum formula: 2-4+5-7/3-4 Rostrum formula: 3-4+7-8/4-6 Rostrum about 0.6 times the carapace length Rostrum about 0.5 times the carapace length Rostrum about 0.7 times the carapace length Eye Pigment in cornea degenerated to a small black dot Nonpigmented in cornea Nonpigmented in cornea Second pereopod Merus 1.3 times longer than carpus Merus nearly as long as carpus Merus subequal in length to carpus Fingers about 1.4 times as long as palm Fingers about twice as long as palm Fingers about twice as long as palm Fingers without any teeth at base Fingers with 1 pair of very small teeth at base Fingers without any teeth at base   Description: Macrobrachium phongnhaense is medium sized shrimp species, maximum length of collected specimens is 39 mm (female). Rostrum straight, reaching 5/7 distal margin of scaphocerite, 0.6 times as long as the carapace, dorsal margin armed with seven or eight teeth, including one to three teeth on carapace behind orbital margin; ventral margin armed without or two teeth (figure 3a). Antennular peduncle about 0.3 and 0.9 times as long as carapace and scaphocerite, respectively. Antennal spine strong developed, situated on lower orbital angle; hepatic spine smaller and inferior to antennal spine. Carapace smooth. Epistome not bilobed. Eyes reduced, small, pigment in cornea degenerated to a small black dot (figure 3a). First pereopod slender, merus about 0.9 times the length of carpus, palm 0.3 times sorter than carpus, finger and palm equal in length (figure 3b). Second prereiopods cyclindrical, equal in length, similar in form, smooth, about 0.5 times length of body; merus 1.3 times longer than carpus, carpus litter longer than palm, palm slightly inflated, fingers about 1.4 time longer than palm, fingers without any teeth at base. (figure 3c). Third pereopod slender, merus 2.1 times longer than carpus, carpus about 0.5 times palm, finger 2.3 times longer than palm (figure 3d). Telson 1.5 times as long as the sixth abdominal somite, with two pairs of spines; two pairs of plumose setae arising from ventral surface of posteromedian tooth; two pairs of setae distinctly longer than lateral pair of spines (figure 3e). Endopod of first pleopod about 1/3 times of exopod length (figure 3f). Appendix masculina of second pleopod longer than appendix interna; appendix interna reaching 3/4 times of appendix masculine (figure 3g). Mouth parts typical of genus (figure 4). Living color: The appendage transparent to translucent; carapace and abdomens whitish to yellowish (figure 5). Habitat: This species lives in streams and standing water in the caves. These caves can be very long, about 4-5 km, such as Va Cave. They are completely without light and water in the cave is mainly from infiltration. Substrate can be silt, muddy or sandy mud. Distribution: Found only in a few caves (Va, 35, Son Doong) in the Phong Nha-Ke Bang National Park, Quang Binh province, Vietnam. Etymology: Shrimp named for location where first obtained in caves in the Phong Nha-Ke Bang National Park. Remarked: The new species is characterized by a transparent body, highly degenerated eyes, smooth and slender second pereiodpods, elongated telson and unarmed preanal region. Morphological comparisons with allied troglobitic congeners are given in table 1.